Comparative characterisation of two nitroreductases from Giardia lamblia as potential activators of nitro compounds. Issue 2 (August 2015) - Müller, Joachim; Rout, Samuel; Leitsch, David; Vaithilingam, Jathana; Hehl, Adrian; Müller, Norbert
Highlights: G. lamblia has two nitroreductases with substrate specificities not only for nitro compounds, but also for quinones. GlNR1 rather activates nitro drugs by forming toxic intermediates, GlNR2 rather inactivates them. Graphical Abstract: Abstract: Giardia lamblia is a protozoan parasite that causes giardiasis, a diarrhoeal disease affecting humans and various animal species. Nitro drugs such as the nitroimidazole metronidazole and the nitrothiazolide nitazoxanide are used for treatment of giardiasis. Nitroreductases such as GlNR1 and GlNR2 may play a role in activation or inactivation of these drugs. The aim of this work is to characterise these two enyzmes using functional assays. For respective analyses recombinant analogues from GlNR1 and GlNR2 were produced in Escherichia coli . E. coli expressing GlNR1 and GlNR2 alone or together were grown in the presence of nitro compounds. Furthermore, pull-down assays were performed using HA-tagged GlNR1 and GlNR2 as baits. As expected, E. coli expressing GlNR1 were more susceptible to metronidazole under aerobic and semi-aerobic and to nitazoxanide under semi-aerobic growth conditions whereas E. coli expressing GlNR2 were susceptible to neither drug. Interestingly, expression of both nitroreductases gave the same results as expression of GlNR2 alone. In functional assays, both nitroreductases had their strongest activities on the quinone menadione (vitamin K3 ) and FAD, but reduction of nitro compounds including the nitro drugs metronidazole and nitazoxanide was clearly detected. Full reduction of 7-nitrocoumarin to 7-aminocoumarin was preferentially achieved with GlNR2. Pull-down assays revealed that GlNR1 and GlNR2 interacted in vivo forming a multienzyme complex. These findings suggest that both nitroreductases are multifunctional. Their main biological role may reside in the reduction of vitamin K analogues and FAD. Activation by GlNR1 or inactivation by GlNR2 of nitro drugs may be the consequence of a secondary enzymatic activity either yielding (GlNR1) or eliminating (GlNR2) toxic intermediates after reduction of these compounds.